Critical thinking skills for your nursing degree - Bottomley, Jane (Senior language tutor); Pryjmachuk, Steven, 1964- (Critical study skills for nursing students., 2018)
An essential text for all those undertaking a nursing degree within higher education, providing study support and skills development for critical thinking, reading and writing.